2011
DOI: 10.1016/j.cognition.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial reasoning in Tenejapan Mayans

Abstract: Language communities differ in their stock of reference frames (coordinate systems for specifying locations and directions). English typically uses egocentrically defined axes (e.g., “left-right”), especially when describing small-scale relationships. Other languages such as Tseltal Mayan prefer to use geocentrically-defined axes (e.g., “north-south”) and do not use any type of projective body-defined axes. It has been argued that the availability of specific frames of reference in language determines the avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 34 publications
2
66
0
2
Order By: Relevance
“…39 Although the use of the absolute uphill/downhill spatial frame of reference may seem awkward from the Western perspective, a recent study on spatial reasoning skills in Tenejapans (Li, Abarbanell, Gleitman & Papafragou, 2011) found that Tzeltal speakers easily solve the languageincongruent problems, and their performance is generally more robust in such tasks than in language-congruent tasks based on the geocentrically-defined coordinates.…”
Section: Spatialization Of Time Across Languages and Culturesmentioning
confidence: 99%
“…39 Although the use of the absolute uphill/downhill spatial frame of reference may seem awkward from the Western perspective, a recent study on spatial reasoning skills in Tenejapans (Li, Abarbanell, Gleitman & Papafragou, 2011) found that Tzeltal speakers easily solve the languageincongruent problems, and their performance is generally more robust in such tasks than in language-congruent tasks based on the geocentrically-defined coordinates.…”
Section: Spatialization Of Time Across Languages and Culturesmentioning
confidence: 99%
“…Therefore, the evidence does not show that any of the participants could not solve the task the other way. In fact, further research showed that both groups could solve the task both ways (Li et al, 2005). The results, though, do show a different preferential understanding of the task, related to the dominant spatial vocabulary.…”
Section: Spatial Terms Influence Nonverbal Spatial Tasksmentioning
confidence: 76%
“…These results indicate that bilingualism may result in the adjustment of bilinguals' sensitivity to their native language construal patterns. In another study, Li et al (2011) conducted four experiments to see whether specific spatial frames of reference in language would prime corresponding spatial conceptualization, specifically in non-linguistic spatial tasks. The participants were members of a Mayan population whose language (Tseltal) uses geocentric spatial frames.…”
Section: Discussionmentioning
confidence: 99%